(untitled) (International relations and international law Journal, 2019)
At the turn of the XX and XXI centuries, attention of the states to the unique opportunities the use of the outer space for economic, defense and scientific purposes provides increased. Rapid progress in the outer space exploration opened a new chapter in the history of the humankind. The last decade of development of the world cosmonautics showed that the previous paradigm of the international legal regulation needs serious upgrading with concepts and criteria of safety of space activities in the near-Earth space. Space activities and their consequences have always had global significance for the safety of the whole world community. The goal of the work is examination of the problems of the environment and space safety legal support. Today the world community faces difficult problems trying to ensure stable development and wishes to have means to provide global safety in the conditions of cardinal dynamic changes in the geopolitical environment and rising of global ecologic threats. One of the anthropogenic factors affecting space activities safety is formation in the outer space of objects that are by convention called «space debris». Observance by the states of guiding principles and rules of prevention of space debris formation adopted by the UN Space Committee will demand active development of the processes of exchange with information among the states concerning national mechanisms regulating and determining solution of this problem – prevention of space debris formation. Scientific importance of the work is determined by its analysis of legal norms of the ecology and discovery of the factors affecting the safety of space activities in the near-Earth space. This article proves the necessity of international cooperation of the states for solution of the problem of environment and outer space pollution. Key words: space debris, pollution of outer space, space security.